Successful treatment of a patient with advanced lung adenocarcinoma (EGFR-T790M and C797S cis) with lazertinib: A case report and literature review - Fang, Yue; Zhang, Qiankun; Wang, Weimin; Tong, Juanjuan; Li, Xialin (Frontiers in Oncology, 2023)
Lazertinib has been shown to treat non-small cell lung cancer (NSCLC) patients with EGFR-T790M, Ex19del, and L858R mutations. However, there are still no studies to prove that lazertinib could be used in patients with EGFR-T790M and C797s cis mutations in NSCLC. We report a case of a patient with advanced lung adenocarcinoma with EGFR-T790M and C797s cis mutations who were treated with lazertinib and achieved satisfactory efficacy without serious side effects. And the scratch assay and colony-forming unit assay were performed using lung adenocarcinoma cells from patients, the results showed that both lazertinib and amivantamab could inhibit the proliferation and migration of lung adenocarcinoma cells to some extent, and the inhibitory effect of lazertinib was better than that of amivantamab (p < 0. 01), while the inhibitory effect of lazertinib combined with amivantamab was not statistically different from that of lazertinib alone(p＞0.05). This finding suggests that lazertinib may be an effective treatment option for patients with lung adenocarcinoma presenting with EGFR-T790M and C797s cis mutations.